Tumor angiogenesis of low-grade astrocytomas measured by dynamic susceptibility contrast-enhanced MRI (DSC-MRI) is predictive of local tumor control after radiation therapy - Fuß, Martin; Wenz, Frederik; Essig, Marco; Münter, Marc; Debus, Jürgen; Herman, Terence S.; Wannenmacher, Michael (International journal of radiation oncology, biology, physics, 2001)
PURPOSE: To assess regional cerebral blood volume (rCBV) as a surrogate marker of angiogenesis in patients with low-grade fibrillary astrocytoma before radiation therapy and to correlate measured values with clinical outcome after fractionated stereotactic radiotherapy (FSRT). - METHODS: Twenty-five patients with histologically proven fibrillary astrocytomas were examined using dynamic susceptibility contrast-enhanced MRI before radiotherapy. Radiotherapy was delivered to mean and median total doses of 60.9 and 60 Gy, respectively (range 55.8-66 Gy). During MRI for treatment planning, 55 T2*-weighted gradient echo images were acquired before, during, and after i.v. contrast-bolus injection. The acquired signal-time curves were converted into concentration-time curves. By normalization to an arterial input function, absolute and relative rCBV values were calculated. Measured pretherapeutic rCBV data were correlated to outcome in terms of local control after FSRT. - RESULTS: Mean pretherapeutic rCBV for astrocytomas was 6.5 +/- 3.7 ml/100 g tissue. Mean and median follow-up times were 47.8 and 52 months, respectively. Fifteen tumors recurred during the period, with a mean and median latency of 39.1 and 42 months, respectively. Tumors recurring earlier than 42 months after FSRT showed a higher pretreatment rCBV than tumors recurring later and tumors in continued local control (8.12 +/- 4.48 ml/100 g vs. 6.0 +/- 2.3 ml/100 g and 4.73 +/- 2.47 ml/100 g; p = 0.02 and p = 0.03). The respective ratios of tumor rCBV in early recurrent tumors to gray matter and white matter rCBV were 0.98 +/- 0.38 and 2.17 +/- 1.36 as compared with 0.79 +/- 0.14 and 1.44 +/- 0.29 in locally controlled tumors (p = 0.074 and p = 0.056). - CONCLUSIONS: In fibrillary low-grade astrocytomas, a noninvasive assessment of angiogenesis as indicated by rCBV measurement was feasible. The present data suggest that high pretherapeutic angiogenic activity in low-grade astrocytomas indicates a subgroup of tumors at higher risk for early local recurrence or malignant transformation after FSRT.
Gesehen am 17.03.2022